Preschool-aged children’s media use and its relationship to their prosocial and aggressive behavior - İnanlı, Seçil. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
The first aim of the study was to have a descriptive data about what preschool children watched and played on the screens including the amount of time they spent for media use, and in which context they consumed media. The second aim of the study was to see if there was a relationship between the duration and the content of media that children used and their prosocial and aggressive behavior. Lastly, the goal of the present study was to explore if children’s time spent for developmentally enriching activities increase or decrease with their time spent for media use. Parents of 52 children aged between 4 and 6 reported their children’s media use on a media diary throughout a weekend and the teachers of the children assessed children’s prosocial and aggressive behavior. The results showed that the aggressive behavior of the children increased as their time spent for playing video games increased. As expected, the time they spent for engaging developmentally enriching activities decreased as the time they spent for playing video games increased. The children’s time spent for media use also increased with their age. The study contributed to the child media literature by considering various factors, such as duration, content, and context, to understand the media use of young children and its relationship to their social behavior among urban Turkish children.
Keywords: Media programs (Education)